Aquifer Characterisation and Vulnerability Assessment in a Typical Basement Complex Terrain - Oluwaseun S. OGUNGBEMI (FUDMA Journal of Engineering and Technology, 2025)
The study employed electrical resistivity surveying using Vertical Electrical Sounding (VES) at 30 locations with a Schlumberger array to evaluate the groundwater potential and aquifer vulnerability within the College of Health Technology, Ijero-Ekiti. Results were presented as maps of resistivity, aquifer thickness, overburden characteristics (TLOA), porosity, hydraulic conductivity, and transmissivity. The resistivity map identifies five zones, with low resistivity (13.105–98.285 ohm-m) in the southern and central areas, indicating shallow, saturated clay-rich aquifers that support hand-dug wells but are prone to contamination. Higher resistivity zones suggest deeper or impermeable materials with lower groundwater potential. Aquifer thickness varies from 1.602 to 11.297 m; thicker zones in the south and center support sustainable yields, while thinner margins are more vulnerable to seasonal drying and pollution. TLOA values (0.702–6.897 m) reflect protective cover; low TLOA zones are highly vulnerable, while higher TLOA regions offer better aquifer protection and long-term supply potential. Longitudinal conductance reveals that high-conductance zones (0.305–0.732 S) in the central area provide strong protection, while low-conductance zones (0.005–0.039 S) in the north and southeast are at risk of contamination. Porosity values (24.156–41.53%) indicate high-porosity zones in the center, which are ideal for groundwater development, although they are more vulnerable. In contrast, low-porosity areas may require deep or fracture-specific drilling. Hydraulic conductivity (0.745–35.276 m/day) and transmissivity (1.835–321.004 m²/day) confirm the central and southern zones as most productive. The study recommends prioritizing borehole siting in zones with high resistivity, thickness, and porosity, implementing contamination controls in vulnerable areas, and integrating multiple hydrogeological parameters for effective groundwater development.